Thinking for themselves?: the effect of informant independence on children’s endorsement of testimony from a consensus - Einav, Shiri (Wiley, 2017)
Testimony agreement across a number of people can be a reassuring sign of a claim’s reliability. However, reliability may be undermined if informants do not respond independently. In this case, social consensus may be a result of indiscriminate copying or conformity and does not necessarily reflect shared knowledge or opinion. We examined children’s emerging sensitivity to consensus independence by testing whether it affected their judgements in a social learning context. Children ages 5, 6 and 8-9 years (N = 92), and 20 adults for comparison, received conflicting testimony about an unfamiliar country from two consensual groups of informants: An independent group who responded privately and a non-independent group who had access to each other’s answers. We found increasing levels of trust in independent consensus with age. Adults and 8-9 year-olds preferred to accept the claims of the independent consensus, whereas 5-year-olds favored the claims of the non-independent consensus and 6-year-olds were mixed. Although previous work has shown that children trust a consensus over a lone dissenter as young as 2 years, the developmental shift in this study indicates that children’s reasoning about the nature of consensus and what makes it reliable continues to develop throughout middle childhood.